Motivasi Kerja dalam Meningkatkan Produktivitas Kerja Pegawai Dinas Perindustrian dan Perdagangan Provinsi Sumatera Utara - Riska Arianti Nasution; Budi Dharma (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In this study, the complexity of motivational factors is closely related to the context of organizational culture, team dynamics, and perceptions of rewards and recognition of individual contributions. Participation in decision-making, opportunities for career development, and interpersonal relationships at work also emerged as important elements in motivating employees. The qualitative analysis highlighted that there is no one-size-fits-all approach to understanding work motivation in this environment. However, the need for recognition of achievement, a sense of involvement in the work process, and support from superiors and coworkers have a significant impact on individuals' motivation levels. This study provides an in-depth understanding of what influences work motivation at the Office of Industry and Trade of North Sumatra Province. The implications of this study emphasize the importance of a sensitive approach to individual needs and preferences in designing effective motivation strategies to improve productivity.